Students’ National Upbringing Research in University of Klaipėda - Sirtautas, Vytautas V. (Acta Paedagogica Vilnensia, 2005)
University’s of Klaipeda students’ today’s culture research is described in the article, data, got in the end of 2002 y., in compared to data, got in the end of 2004 y. National upbringing’s dimension is analysed. In two years’ time social trauma in Lithuania 174 influence to academic youth has decreased: established, e.g., that there are a one third less students, who liked Lithuanian nation at the same time estimating it negative; the amount of students, who are favourably disposed towards their own nation, increased by one third. It showed up, that fathers educate their children more patriotically than mothers; unfortunately, men do not socialize with children enough. It was ascertained, that it is hard to educate youth patriotically because of the particularity of work in high school, but students’ national optimism can be raised. Lithuanian schools do not manage to indoctrinate love to native land worth – it stays in the last place among the students in the first courses and is important only for every fifteenth student. With reference to working practice, it can be stated, that this worth should be indoctrinated from as early as possible, even before school. Despite the agitations, specific to international political unions, it is necessary to impose patriotic education course for pedagogical profile specialities’ students in Lithuanian high schools.